La visibilidad académica de la exclusión: descripción de un practicum desde la optatividad de Trabajo Social - Bueno Abad, José Ramón; Arrando los Santos, Teresa (Cuadernos de Trabajo Social, 2008)
The present paper approaches the academicals experience that let to do the training credits of subjects such as Social Psychology of Maladjustment and Psychosocial Intervention. These subjects are optative in the studies planning of Social Work at University of València imparted by the professor José R. Bueno Abad. The aim is that the Social Work students do a practicum in institutional centres mainly in Cáritas Diocesana de Valencia. During this period student are involved in several programmes leading to homeless, mental ills, HIV-AIDS ills, and immigrants. Eventually, try to create a space of reflection about the exclusion problem: conceptions, typologies, present social policies in course to fight against it, and to urge a discussion about the incidence of Social policies in collectives of exclusion risk.